Evaluasi Pengendalian Persediaan WIP dengan Metode Production Order Quantity (POQ) di Perusahaan Manufaktur Ban - Puspasari, Luky; Hasibuan, Sawarni (Universitas Teuku Umar, 2024)
The inventory system throughout the supply chain network must be effectively controlled, making Work in Process (WIP) inventory control essential. In tire manufacturing, Green Tire inventory holds the highest WIP value and is consistently maintained. However, inconsistent order quantities have resulted in uncontrolled inventory levels, leading to overstock in the storage area. This study aims to analyze the priority categories of Green Tire inventory, evaluate the optimal order quantities, and compare total inventory costs to minimize the overall cost. The methods used include ABC Analysis and Production Order Quantity (POQ) with safety stock, applying service levels of 93%, 90%, and 80% for A, B, and C categories, respectively. The findings indicate that Green Tire inventory class A accounts for 65% of the volume and 67% of the total inventory value, class B for 23% of the volume and 28% of the value, and class C for 11.9% of the volume and 5% of the value. Implementing the POQ method standardizes order quantities across rim codes, reducing maximum inventory levels by up to 69.38%. Total storage cost savings reached 66.15%, with only a 0.2% increase in setup costs. The POQ method achieved total inventory cost savings of 52.37% for Green Tire inventory.